Invention and Implementation of NTBS Clustering Protocol for VANET - Nampally, Venkatamangarao; Sharma, M. Raghavender (International Journal of Computer Sciences and Engineering, 2025)
Vehicular Ad hoc Networks (VANETs) are the promising approach to provide traffic, safety and other applications to the drivers as well as passengers. It becomes a key component of the intelligent transport system. Communication is not for only reliable data delivery but also the achieving the reliability. In this paper, we present how to obtain best communication in VANET system by using Transitive Trust Relationships concept and thus improving the performance of the authentication procedure of the whole network in a cluster. Proposed NTBS protocol not only adapts the concept of Transitive Trust Relationships but also improves the performance of the authentication procedure and it provides best communication with good security. We implement NTBS protocol in NS2 Simulator. NS2 is open source and discrete event-driven, object-oriented and freely available simulation tool to simulate and analyze dynamic nature of communication networks. It is also a powerful tool to develop new protocols and functions. It provides support for OSI and TCP/IP protocols stack and many standard routing and application protocols for wire and wireless networks. NAM is used to display the process of simulation.